Extended Erythropoietin Treatment Prevents Chronic Executive Functional and Microstructural Deficits Following Early Severe Traumatic Brain Injury in Rats - Robinson, Shenandoah; Winer, Jesse L.; Chan, Lindsay A. S.; Oppong, Akosua Y.; Yellowhair, Tracylyn R.; Maxwell, Jessie R.; Andrews, Nicholas; Yang, Yirong; Sillerud, Laurel O.; Meehan, William P.; Mannix, Rebekah; Brigman, Jonathan L.; et al. (Frontiers in Neurology, 2018)
Survivors of infant traumatic brain injury (TBI) are prone to chronic neurological deficits that impose lifelong individual and societal burdens. Translation of novel interventions to clinical trials is hampered in part by the lack of truly representative preclinical tests of cognition and corresponding biomarkers of functional outcomes. To address this gap, the ability of a high-dose, extended, post-injury regimen of erythropoietin (EPO, 3000U/kg/dose x 6d) to prevent chronic cognitive and imaging deficits was tested in a postnatal day 12 (P12) controlled-cortical impact (CCI) model in rats, using touchscreen operant chambers and regional analysis of diffusion tensor imaging (DTI). Results indicate that EPO prevents functional injury and MRI injury after infant TBI. Specifically, subacute DTI at P30 revealed widespread microstructural damage that is prevented by EPO. Assessment of visual discrimination on a touchscreen operant chamber platform demonstrated that all groups can perform visual discrimination. However, CCI rats treated with vehicle failed to pass reversal learning, and perseverated, in contrast to sham and CCI-EPO rats. Chronic DTI at P90 showed EPO treatment prevented contralateral white matter and ipsilateral lateral prefrontal cortex damage. This DTI improvement correlated with cognitive performance. Taken together, extended EPO treatment restores executive function and prevents microstructural brain abnormalities in adult rats with cognitive deficits in a translational preclinical model of infant TBI. Sophisticated testing with touchscreen operant chambers and regional DTI analyses may expedite translation and effective yield of interventions from preclinical studies to clinical trials. Collectively, these data support the use of EPO in clinical trials for human infants with TBI.